Extraction of interaction and physical design principles as guidelines in designing wearable technology for individual with autism / Mohamad Isa Ab Malik ... [et al.] - Ab Malik, Mohamad Isa; Ahmad, Siti Zulaiha; Md Nor, Romiza; Jamil, Nursuriati; Idris, Sakinah; Wahid, Noorhaniza; Liew, Bee Wah (UiTM Cawangan Perlis, 2024)
Autism Spectrum Disorder is a neurodevelopmental condition characterized by challenges in social interaction, communication, and behavior, with each individual exhibiting unique characteristics due to the diverse symptoms and varying severity levels across the spectrum. Individuals with autism often face difficulties in behavior, communication, and interaction, occasionally leading to stress and tantrums due to their limited verbal expression of emotions. Traditional methods such as therapy and medication have not been enough to fully help individual with autism. Nowadays, technology, especially wearable technology offers promising opportunities for autism intervention. Recognizing their unique characteristics, this study aims to explore the wearable technology design principles that will cater their needs. Two common concepts which are the interaction and physical design components have been identified as essential in the designing the wearable technology for individual with autism. The extraction of the elements and design principles for both components have been done through an extensive process involving literature reviews and focus group discussions. After the validation process through an expert review survey, four key elements for each component, along with their respective design principles, are proposed by the study. The interaction design component includes navigation tools, feedback, direct manipulation, and multimedia elements, while the physical design component comprises material, screen display, safety, and portability. The proposed components, elements, and design principles outlined in this paper will serve as a valuable guideline in designing wearable technology to effectively meet the distinctive needs of individuals with autism.